Pengaruh Pemberian Edukasi Kesehatan Menggunakan Booklet Pada Pengetahuan Ibu Hamil Tentang Kegawatdaruratan Janin Dan Ibu Hamil Di Wilayah Kerja Puskesmas Sukaraja Kota Bandar Lampung Tahun 2025 - Amartya, Salsa Anastasya; Wardiyah, Aryanti; Wandini, Riska; Rilyani (Jurnal Keperawatan Muhammadiyah, 2025)
Introduction : The Sukaraja Community Health Center had the most maternal mortality rate, namely 2 cases, and the Segalamider Community Health Center had 2 cases. Apart from that, in 2023 the number of pregnant women in Bandar Lampung City will be 19,729, of which Panjang Health Center is in first place with 1,484 (7.52%), in second place is Sukaraja Health Center 1,128 (5.71%), and in third place is Satellite Health Center with 1,056 (5, 35%) Objective : The effect of providing health education using booklets on the knowledge of pregnant women in handling emergencies for the fetus and pregnant women in the working area of the Sukaraja Health Center in Bandar Lampung City in 2025 is known. Method: Type of quantitative research by design pre-experimental with approach one group pre-test and post-test. The population of this study was 249 respondents and the total sample for this study was 154 respondents from pregnant women in the working area of the Sukaraja Community Health Center, Bandar Lampung City. Results: After the t-dependent test was carried out, a p-value of 0.000 < 0.05 was obtained. There was an increase in knowledge about fetal emergencies and pregnant women at the Sukaraja Health Center increased by around 47%. Conclusion: There is an influence of health education about fetal and pregnant women emergencies at the Sukaraja Health Center, Bandar Lampung City in 2025